Developing a facilitated reflection tool using video technology, during a laparoscopic simulation activity, for doctors in postgraduate obstetrics & gynaecology training - Subramanian, Venkatesh (2020)
The evidence for laparoscopic simulation as an effective educational intervention is well established with benefits such as shortening the learning curve, increased learner self-efficacy and developing surgical skills without compromising patient safety.